Art and Expressive Therapies Within the Medical Model : Clinical Applications - Elkis-Abuhoff, Deborah, editor 653223; Gaydos, Morgan, editor 653224 (New York : Routledge, 2019)
Art and Expressive Therapies Within the Medical Model explores how to best collaborate across disciplines as art and expressive therapists continue to become increasingly prevalent within the medical community. This collection of diverse chapters from seasoned practitioners in the field introduces readers to art therapy interventions across a variety of artistic approaches, patient demographics, and medical contexts, while paying special attention to new approaches and innovative techniques. This is a cutting-edge resource that illustrates the current work of practitioners on a national and global level while providing a better understating of the integration of biopsychosocial approaches within art and expressive therapies practice.